Assessment of factors affecting safety culture in Yazd steel industry workers - Gh Halvani; M Ebrahimzadeh; M Dehghan; H Fallah; M Mortazavi (طب کار)
Background: Safety culture is a factor that because of it all of workers from headmaster to simple workers come together so that they could contribute to the safety of themselves and their coworkers. The purpose of this study was to evaluate factors affecting safety culture in Yazd steel industry workers. Methods: This study was conducted on 244 steel industry workers. In this cross-sectional study, data was gathered by a questionnaire. This questionnaire consisted of 75 questions in the form of multiple choice questions (standard safety culture questionnaire) and 6 questions about accidents (accident questionnaire). Data was gathered and after being coded was entered into SPSS software for analysis. Results: In this study there was a significant relationship between safety culture and educational level and work experience (p-value<0.05). There wasn’t a significant relationship between safety culture and age, marital status, work shift and location of body involved. In this study the most frequent cause of occupational accidents was burning (25%) and upper extremities were the organs most frequently injured. Conclusion: In order to achieve system requirements about safety, it is necessary to implement a proper structure and in order to match individuals with this structure, culture change and behavior change should be used.